2024
DOI: 10.18632/aging.205541
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A alleviates ferroptosis by activating the Nrf2/HO-1 signaling pathway in traumatic brain injury

Junwei Kang,
Bingkai Ren,
Lianghua Huang
et al.

Abstract: Background: Traumatic Brain Injury (TBI) has high disability and mortality rate. Oxidative stress and ferroptosis are important pathophysiological characteristics after TBI. Orexin-A (OXA) can alleviate neuronal damage in diverse neurological disorders. Nevertheless, the role and mechanism of OXA in TBI stay unknown. Objectives: The research investigated protection influence of OXA on TBI and its potential mechanisms. Methods: Male Sprague-Dawley rats were randomly grouped into: sham, TBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In this sense, such chemical reactions can be spontaneous or catalyzed stereospecific by lipoxygenase (LOX) enzymes. Thus, the binding of the LOX15 complex (ALOX15, 15-LOX) with the phosphatidylethanolamine (PE) binding protein (PEBP1) promotes ferroptosis in some contexts [202][203][204][205].…”
Section: Ferroptosismentioning
confidence: 99%
“…In this sense, such chemical reactions can be spontaneous or catalyzed stereospecific by lipoxygenase (LOX) enzymes. Thus, the binding of the LOX15 complex (ALOX15, 15-LOX) with the phosphatidylethanolamine (PE) binding protein (PEBP1) promotes ferroptosis in some contexts [202][203][204][205].…”
Section: Ferroptosismentioning
confidence: 99%
“…Orexin-A has been identified as a novel angiogenic peptide, promoting blood vessel formation by activating the MEK/ERK1/2 signaling pathway through Orexin-A receptor activation [ 12 ]. Our previous studies have shown that Orexin-A has the potential to ameliorate brain tissue damage in rats with TBI [ 13 ]. However, the relationship between Orexin-A and angiogenesis in TBI is still insufficient.…”
Section: Introductionmentioning
confidence: 99%